Development of modules macromolecules based on local natural resources of Maluku in project-based learning for XII grade senior high school students - Vivian Salelatu; Eli Rohaeti (Pascasarjana Universitas Negeri Medan, 2023)
This research aims to develop chemistry learning modules based on local natural resources in Maluku in project-based learning on macromolecular material class XII IPA SMA. This research refers to the 4-D development model by Thiagarajan, Semmel, and Semmel, which includes the stages of define, design, develop, and disseminate. This learning module has gone through the validation stage by expert validators. It has gone through field trials and has been revised by developers to produce a valid and practical learning module. The results of this study are: (1) validity assessment by one media expert and one material expert is in the very valid category with an average score from material experts of 4.49 and an average score from media experts of 4.68; (2) the small group trial to 9 students of class XII IPA 1 SMAN 6 Ambon obtained a percentage of 93.6% in the very practical category; (3) Field trials to 30 students of class XII IPA 3 SMAN 12 Ambon resulted in a percentage of 90.2% with a very practical category. The response of five chemistry teachers to the developed module also resulted in a percentage of 85.4% in the very practical category. In conclusion, the chemistry learning module based on local natural resources in Maluku in project-based learning developed with a 4-D model is valid, practical, and It can be used as teaching materials in school.Keywords: Local natural resources; Module development; Macromolecules; Project-based learning; 4D model